Omics Technology for Genetic Selection Towards Feed Efficiency Traits of Indigenous Cattle in Indonesia: A Review - Hendrawan Soetanto; Fatchiyah (Jurnal Nutrisi Ternak Tropis, 2023)
Indigenous cattle in Indonesia seldom to reach their genetic potentials due to an interaction impact of harsh tropical climate and low-quality feed. Some indigenous breeds of cattle in Indonesia, such as Bali, Madura and Crossbred Ongole have demonstrated their successful adaptation to survive in the harsh environment, but their ultimate performances are still considered less than their genetic potentials when reared under comfortable environment like in the sub-tropical climate. This is primarily due to inefficient fermentation of feed originating from inadequate supply of essential nutrients required for optimum growth of microbes in the forestomach. A rapid advancement of omics technology has been the driver for ruminant nutritionists to use such a technology to study the interrelationship between nutrients and particular genes associated with the biochemical pathways of nutrients at molecular levels. This review highlights the current issues and challenges on the use of omics technologies to improve the efficiency of feed utilization by cattle consuming low-quality diets and its potential to be used in the genetic selection program.